Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11011-017-9970-y
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates surgery-induced cognitive dysfunction in aged mice

Abstract: Post-operative cognitive dysfunction (POCD) is associated with elderly patients undergoing surgery. However, pharmacological treatments for POCD are limited. In this study, we found that curcumin, an active compound derived from Curcuma longa, ameliorated the cognitive dysfunction following abdominal surgery in aged mice. Further, curcumin prevented surgery-induced anti-oxidant enzyme activity. Curcumin also increased brain-derived neurotrophic factor (BDNF)-positive area and expression of pAkt in the brain, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…These candidates include anti‐inflammatory agents such as RAGE antagonist FPSZM1, berberine, microglia activation inhibitor minocyclin, anti‐inflammatory cytokine IL‐4, and glycyrrhizin, a natural high‐mobility group box 1 (HMGB1) inhibitor . Another type of agents are oxidative stress inhibitors such as curcumin, edaravone, and apocynin . In clinical study, intraoperative dexmedetomidine was reported to reduce the incidence of PND along with decreased levels of β‐amyloid and Tau protein accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…These candidates include anti‐inflammatory agents such as RAGE antagonist FPSZM1, berberine, microglia activation inhibitor minocyclin, anti‐inflammatory cytokine IL‐4, and glycyrrhizin, a natural high‐mobility group box 1 (HMGB1) inhibitor . Another type of agents are oxidative stress inhibitors such as curcumin, edaravone, and apocynin . In clinical study, intraoperative dexmedetomidine was reported to reduce the incidence of PND along with decreased levels of β‐amyloid and Tau protein accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…In the same perspective, curcumin, an active ingredient of plant Curcuma longa, is apparently effective in treating POP related to GA and surgery in human (Agarwal et al 2011;Maulina et al 2018), and in mice (Sahbaie et al 2014). As well as suppressing of neuro-in ammatory activation associated with neurodegenerative diseases (Sundaram et al 2017), and preventing anesthetics exposure-induced POCD in mice (Ji et al 2015;Wu et al 2017). The effects of curcumin were probably prompted by enhancing the anti-oxidant enzyme activity, and activation of BDNF (Wu et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences have confirmed that DM is a major pathogenesis factor for cognitive deficits . Curcumin has been shown to be an effective agent for attenuating diabetic encephalopathy and improving surgery‐induced cognitive dysfunction in mice . In this study, we first explored the effects of the curcumin derivative NC on learning and memory performances of rats with DM induced by STZ.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,26 Curcumin has been shown to be an effective agent for attenuating diabetic encephalopathy and improving surgery-induced cognitive dysfunction in mice . 17,18,27 In this study, we first explored the effects of the curcumin derivative NC on learning and memory performances of rats with DM induced by STZ. Our results revealed that the declined cognitive functions in DM rats were significantly reserved by NC treatment, as evidenced by decreases in escape latency as well as increases in times across target quadrant in MWM test, and elevated DI in the novel object recognition test.…”
Section: Discussionmentioning
confidence: 99%